2023
DOI: 10.1101/2023.07.31.551363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A robust method for measuring aminoacylation through tRNA-Seq

Abstract: Current methods to quantify the fraction of aminoacylated tRNAs, also known as the tRNA charge, are limited by issues with either low throughput, precision, and/or accuracy. Here, we present an optimized charge tRNA-Seq method that combines previous developments with newly described approaches to establish a protocol for precise and accurate tRNA charge measurements. We verify that this protocol provides robust quantification of tRNA aminoacylation and we provide an end-to-end method that scales to hundreds of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… 40 47 Recently, this strategy has been combined with modern enrichment and sequencing methods to perform such analyses in a more high-throughput manner. 42 , 43 , 45 47 After the selective periodate-mediated oxidation of the uncharged tRNAs and the deacylation of the charged tRNAs using mildly alkaline conditions, a unique oligonucleotide sequence can be introduced onto the intact 3′-terminus of the acylated population either through ligation 43 , 45 , 46 or by polymerase-mediated extension of the 3′-terminus using a DNA template that is hybridized onto the tRNA sequence. 44 The installed oligonucleotide sequence can be subsequently used to selectively reverse-transcribe and PCR amplify the charged tRNA sequences.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 40 47 Recently, this strategy has been combined with modern enrichment and sequencing methods to perform such analyses in a more high-throughput manner. 42 , 43 , 45 47 After the selective periodate-mediated oxidation of the uncharged tRNAs and the deacylation of the charged tRNAs using mildly alkaline conditions, a unique oligonucleotide sequence can be introduced onto the intact 3′-terminus of the acylated population either through ligation 43 , 45 , 46 or by polymerase-mediated extension of the 3′-terminus using a DNA template that is hybridized onto the tRNA sequence. 44 The installed oligonucleotide sequence can be subsequently used to selectively reverse-transcribe and PCR amplify the charged tRNA sequences.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, with translation blocked (puromycin treatment), hydrolysis of Ser-tRNA Ser by hAlaX was more pronounced. Finally, two independent reports using the DM-tRNA-seq (demethylase-thermostable group II intron RT tRNA sequencing) method showed that the aminoacylation levels of tRNA Ser isoacceptors are the lowest among all human tRNAs ( 65 , 66 ). The rationale for the low levels of Ser-tRNA Ser compared with other tRNAs ( 65 , 66 ) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two independent reports using the DM-tRNA-seq (demethylase-thermostable group II intron RT tRNA sequencing) method showed that the aminoacylation levels of tRNA Ser isoacceptors are the lowest among all human tRNAs ( 65 , 66 ). The rationale for the low levels of Ser-tRNA Ser compared with other tRNAs ( 65 , 66 ) is unclear. Whether hydrolysis of Ser-tRNA Ser by hAlaX is responsible for the low tRNA Ser charging levels in vivo requires further investigation.…”
Section: Discussionmentioning
confidence: 99%